Review of the European species of Diglyphus Walker (Hymenoptera: Eulophidae) including the description of a new species - Hansson, Christer; Navone, Paolo (Zootaxa, 2017)
The European species of Diglyphus Walker are reviewed. Fifteen species are included. One of these, D. clematidis sp. n., is described as new, and one, D. anadolucus Doganlar, is recorded as new to Europe. Several of the species have their geographical distribution increased as many new country records are introduced. New host records and compilation of host records from the literature are presented in tables. To facilitate the identification of the species a key and numerous illustrations are included. The identity of one of the species described from Europe, D. phytomyzae Ruschka, is unclear. It has not been possible to locate the type material of this species and the original description is not detailed enough to make an unambiguous interpretation possible. Two species, D. scapus Yefremova from Iran and D. sensilis Yefremova from Turkey, are discussed as they occur in the vicinity of Europe.